IMPLICATIONS OF DIFFERENCES IN POLITICAL BACKGROUNDS ON REGIONAL HEAD LEADERSHIP MODELS - Muhammad Rizki Irfani; Agus Joko Pitoyo; Ahmad Romadhoni Surya Putra (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The success of local development depends on a leadership that is able to transform and collaborate with society in order to optimize its potential. In practice, success programs often do not continue due to regional heads change. Differences in vision or political backgrounds could disrupt the leadership transfer process and policy sustainability. Banjarbaru city can be an example of how leadership transitions from regional head with a bureaucrat background to regional head with a politician background. This research aims to understand the implications of differences in political background on the leadership models used by regional heads. Qualitative methods are used in this research, with regional heads as the research object. The results of the study found that differences in political backgrounds do not necessarily mean that the leadership models used are completely different. The model is more influenced by situational conditions in the region. Thus, it can be concluded that political background becomes social capital that can support the achievement of political interests and provide color to the leadership model they choose.